Peran Pendidikan Agama Islam dalam Meningkatkan Karakter Siswa Madrasah Ibtidaiyah di Bengkulu - Aida Susanti; Asraf Yasid; Mersi Titi Sari; Dea Meike Dwi Putri; Inndi Sifa Urrohmah; Elisah Veby Alvita (Al-Khair Journal: Management Education, 2024)
Abstract: Islamic religious education has not played an optimal role, characterized by a moral crisis in students, and the professionalism of teachers is still weak. The purpose of this paper is to map and analyze the role of Islamic religious education in improving students' character. Using a descriptive qualitative method. The data sources are both primary data and secondary data. The results of the study can be concluded that in general, Islamic religious education has played a sufficient role in improving the character of students, Islamic religious education is used as the foundation of moral education for the nation's children, forming the attitude and behavior of student tolerance such as mutual respect, mutual respect, mutual help, mutual cooperation, mutual care, mutual advice, but the role is not optimal, there are still human resources still less professional and lacking quality, the welfare of educators is still low, the learning orientation is more cognitive, the approach to learning methods is still weak, the cost of education is still relatively low, resulting in the character of students not improving and even becoming a serious threat to the next generation which is increasingly uneven. Thus, it can be suggested that to improve the character of students, then increase the role of Islamic religious education in madrasas.Keywords: The Role of Islamic Religious Education, Student Character, Madrasah Ibtidaiyah Abstrak: Pendidikan agama Islam belum berperan secara optimal, ditandai dengan terjadinya krisis moral pada siswa, dan profesionalitas guru masih lemah. Tujuan tulisan ini untuk memetakan dan menganalisis peran pendidikan agama Islam dalam meningkakan karakter siswa. Menggunakan metode kualitatif deskriptif. Sumberdata baik data primer maupuan data skunder. Hasil penelitian dapat disimpulkan bahwa secara umum pendidikan agama Islam telah cukup berperan dalam meningkatkan karakter siswa, pendidikan agama Islam dijadikan sebagai pondasi pendidikan moral anak bangsa, membentuk sikap dan perilaku toleransi siswa seperti saling menghormati, saling menghargai, saling tolong menolong, gotong royong, saling menjaga, saling menasehati dalam kebaikan, namun perannya belum optimal, masih terdapat sumberdaya manusia masih kurang professional dan kurang berkualitas, kesejahteraan tenaga pendidik masih rendah, orientasi pembelajaran lebih bersifat kognitif, pendekatan metode pembelajaran masih lemah, biaya pendidikan masih tergolong rendah, sehingga mengakibatkan karakter siswa belum meningkat bahkan menjadi ancaman serius bagi generasi berikutnya yang semakin senjang. Dengan demikian dapat disarankan, bahwa untuk meningkatkan karakter siswa, maka tingkatkan peran pendidikan agama Islam di madrasah.Kata kunci: Peran Pendidikan Agama Islam, Karakter Siswa, Madrasah Ibtidaiyah